Pengaruh Model Problem Based Learning Terhadap Kemampuan Pemecahan Masalah Matematis Siswa SMP Negeri 3 Prabumulih - Arista, Vevitri; Jumroh, Jumroh; Kesumawati, Nila (JAMPARING: Jurnal Akuntansi Manajemen Pariwisata dan Pembelajaran Konseling, 2024)
This research aims to determine the effect of the problem-based learning model on the mathematical problem-solving abilities of students at SMP Negeri 3 Prabumulih. This research was conducted at SMP Negeri 3 Prabumulih for the 2023/2024 academic year. The research sample was obtained from two classes consisting of an experimental class (PBL) of 32 students and a control class (conventional) of 32 students. Data collection after treatment was done using tests of students' mathematical problem-solving abilities. From the results of the research and discussion, it can be concluded that there is an influence that the mathematical problem-solving skills of students taught using the problem-based learning model are higher than those of students taught.